Remote Control Pada Robot Mobile Pembersih Lantai Menggunakan Smartphone Dengan Kendali Sensor Accelerometer - Tengku Musri; Muhamad Nasir (Jurnal Teknologi Informasi dan Terapan, 2019)
Technological developments are needed in the completion of a job both working automatically and manually with good results. In this need, a technology is used which has certain advantages in a matter. For example, a room cleaning device that is a vacuum cleaner that is often used by housewives to clean dirt and dust is used because it can ease the work, the vacuum cleaner that is currently in use by manual and automatic. This study proposes a controlling mobile vacuum cleaner by utilizing an accelerometer sensor found on a smartphone with Bluetooth communication media between robots and smartphones. An accelerometer is used to control the motion of a robot by taking changes in values from the slope angles X, Y and Z. With the vaccum cleaner robot, it is hoped that it can provide better work results in cleaning the room from dirt and dust, as well as providing convenience in controlling the vaccum cleaner robot for ordinary people. From the results of manual control trials on the robot, the accuracy of the control accuracy is 95%. The maximum range of Bluetooth signals reaches 30 meters without obstacles and there are obstacles. This vacuum cleaner robot can suck up dirt in the form of torn paper, sugar and coffee.